Allosteric mechanism of Ca(2+) activation and H(+)-inhibited gating of the MthK K(+) channel - Pau, Victor P.T. (The Rockefeller University Press, 2010)
MthK is a Ca(2+)-gated K(+) channel whose activity is inhibited by cytoplasmic H(+). To determine possible mechanisms underlying the channel’s proton sensitivity and the relation between H(+) inhibition and Ca(2+)-dependent gating, we recorded current through MthK channels incorporated into planar lipid bilayers. Each bilayer recording was obtained at up to six different [Ca(2+)] (ranging from nominally 0 to 30 mM) at a given [H(+)], in which the solutions bathing the cytoplasmic side of the channels were changed via a perfusion system to ensure complete solution exchanges. We observed a steep relation between [Ca(2+)] and open probability (Po), with a mean Hill coefficient (n(H)) of 9.9 ± 0.9. Neither the maximal Po (0.93 ± 0.005) nor n(H) changed significantly as a function of [H(+)] over pH ranging from 6.5 to 9.0. In addition, MthK channel activation in the nominal absence of Ca(2+) was not H(+) sensitive over pH ranging from 7.3 to 9.0. However, increasing [H(+)] raised the EC(50) for Ca(2+) activation by ∼4.7-fold per tenfold increase in [H(+)], displaying a linear relation between log(EC(50)) and log([H(+)]) (i.e., pH) over pH ranging from 6.5 to 9.0. Collectively, these results suggest that H(+) binding does not directly modulate either the channel’s closed–open equilibrium or the allosteric coupling between Ca(2+) binding and channel opening. We can account for the Ca(2+) activation and proton sensitivity of MthK gating quantitatively by assuming that Ca(2+) allosterically activates MthK, whereas H(+) opposes activation by destabilizing the binding of Ca(2+).